Relationship among Bilirubin Levels Measured Using Three Methods of Transcutaneous, Serum, and Kramer's Scale in Term Neonates - Sara Esmaelzadeh -Saeieh; Mehrnaz Asgaripoor; Kourosh Kabir; Alireza Jashni Motlagh (Mashhad University of Medical Sciences, 2022)
Background: The measurement of total serum bilirubin is a stressful diagnostic method; therefore, it is necessary to measure bilirubin levels using non-invasive ways. The present study aimed to assess the relationship between bilirubin levels measured using three methods of transcutaneous, serum, and Kramer's scale in term neonates with jaundice. Methods: This descriptive-analytical study was conducted on 180 full-term neonates admitted to Imam Ali Hospital in Alborz province, Iran. Bilirubin level was measured by three methods of serum, transcutaneous (using MBJ20, B&M Technology Co., China), and Kramer's scale (based on the appearance) before phototherapy. Thereafter, the relationship between serum bilirubin levels using transcutaneous and Kramer's scale was determined by the Pearson and Spearman correlation coefficients. Results: The correlation coefficient between serum bilirubin and transcutaneous bilirubin (TCB) was obtained at 0.915 before phototherapy. Furthermore, the correlation coefficients between serum bilirubin and TCB were calculated at 0.881 and 0.77 in the covered and uncovered areas after phototherapy, respectively. The correlation coefficient between TCB in the covered and uncovered areas was 0.81. The mean difference between serum bilirubin and TCB was 0.42±1.25 before phototherapy. Moreover, the mean difference values between serum bilirubin and TCB were reported as 1.36±1.37 and 83.1±63.4 in the covered and uncovered areas after phototherapy, respectively. Conclusion: As evidenced by the obtained results, there was a significant correlation between TCB and serum bilirubin before the initiation of phototherapy. Therefore, it is recommended to use TCB instead of repeated blood sampling to follow and monitor neonates.